(untitled) (Baghdad Science Journal, 2020)
Water Quality Index (WQI) as a tool to assess the water quality status provides advice related to the use of water quality monitoring data and it is a way for combining the complex water quality data into a single value or single statement.The present study was conducted on Al- Hilla river in the middle of Iraq from August 2012 to July 2013 at five selected stations in the river, from Al- Musaib city to Al- Hashimya at the south of Hilla to determine its suitability for aquatic environment (GWQI), drinking water (PWSI) and irrigation (IWQI).This index offers a useful representation of the overall quality of water for public or any intended use as well as indicating pollution, water quality management, and decision making. According to the obtained results, it can be concluded that the EC, TSS, Total hardness, Ca, Mg, DO, BOD5, and NO3 moved away from the desired standards when the temperature rises. The variable of value of this index may be due to increasing the ration of organic matters and converting the carbonate to bicarbonate. The results recorded high value of calcium and magnesium more than the standard value of WHO and IQS (50 mg/l and high value of total hardness more than 500 mg/l). Irrigation water quality index (IWQI) in the study sites were ranged between 66-83 ranged between fair and good.